2010
DOI: 10.1038/ismej.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomics of bathypelagic plankton and bottom sediment from the Sea of Marmara

Abstract: To extend comparative metagenomic analyses of the deep-sea, we produced metagenomic data by direct 454 pyrosequencing from bathypelagic plankton (1000 m depth) and bottom sediment of the Sea of Marmara, the gateway between the Eastern Mediterranean and the Black Seas. Data from small subunit ribosomal RNA (SSU rRNA) gene libraries and direct pyrosequencing of the same samples indicated that Gamma-and Alpha-proteobacteria, followed by Bacteroidetes, dominated the bacterial fraction in Marmara deep-sea plankton,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 74 publications
7
111
0
2
Order By: Relevance
“…As expected from their high relative abundance in deep-ocean ecosystems Martín-Cuadrado et al, 2007), most of these HGT involved proteobacterial donors but also, and more surprisingly, Firmicutes and Chloroflexi (Figures 3a and b). Although much less frequent than Proteobacteria, both groups are relatively abundant in deep waters of the Mediterranean basin (Martín-Cuadrado et al, 2007;Quaiser et al, 2011). These genes of bacterial origin, which are scattered in the genomic fragments analysed (Figure 1), are often shared by a variety of thaumarchaeotal species, including C. symbiosum and N. maritimus, suggesting that the HGT events are ancient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected from their high relative abundance in deep-ocean ecosystems Martín-Cuadrado et al, 2007), most of these HGT involved proteobacterial donors but also, and more surprisingly, Firmicutes and Chloroflexi (Figures 3a and b). Although much less frequent than Proteobacteria, both groups are relatively abundant in deep waters of the Mediterranean basin (Martín-Cuadrado et al, 2007;Quaiser et al, 2011). These genes of bacterial origin, which are scattered in the genomic fragments analysed (Figure 1), are often shared by a variety of thaumarchaeotal species, including C. symbiosum and N. maritimus, suggesting that the HGT events are ancient.…”
Section: Resultsmentioning
confidence: 99%
“…The fact of retrieving Chloroflexi as the second most frequent donor (19 cases, Figures 4b and 5b), in particular in libraries AD1000 and KM3 (10 and 8 cases, respectively), but also in whole fosmid gene phylogenies, might appear more surprising. Nevertheless, as mentioned above, this phylum is relatively abundant in the deep Mediterranean Sea (Martín-Cuadrado et al, 2007;Quaiser et al, 2011), which makes it a likely alternative donor. Other groups (Actinobacteria, Acidobacteria, Bacteroidetes, Cyanobacteria, Firmicutes, Planctomycetes and Verrucomicrobia) appeared to have also contributed with several genes to the genomes of planktonic marine archaea (Figures 4b and 5c).…”
Section: Resultsmentioning
confidence: 99%
“…Since that early work was published, many estimates of average microbial genome size from metagenomic data have been reported (Figure 2; Frank and Sorensen, 2011;Oh et al, 2011;Quaiser et al, 2011;Xia et al, 2011;Eiler et al, 2013). Estimates of average genome size from metagenomic data have now been reported for many systems, including fresh water, brackish water and aquifers (Figure 2).…”
Section: Streamlining Theorymentioning
confidence: 99%
“…Metagenomes from ALOHA were previously described in Shi et al (2011). Data were also analyzed from 454 metagenomic sequences collected from Eastern Tropical South Pacific Oxygen Minimum Zone (Stewart et al, 2012), the Puerto Rico Trench (Eloe et al, 2011a), the Sea of Marmara (Quaiser et al, 2010) and the Matapan-Vavilov Deep in the Mediterranean Sea (Smedile et al, 2013). All raw data were trimmed of low-quality end sequences using Lucy (Chou and Holmes, 2001) and de-replicated using CDHIT-454 (Fu et al, 2012).…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…Bacterioplankton of the SAR11 clade are the most numerous in marine systems, typically comprising B25% of all prokaryotic cells (Morris et al, 2002;Schattenhofer et al, 2009). Although the majority of research has focused on the SAR11 clade in the euphotic and upper mesopelagic zones, multiple studies have demonstrated evidence of substantial SAR11 populations deeper in the mesopelagic, as well as in the bathy-and even hadopelagic (46000 m) realms (Martin-Cuadrado et al, 2007;Konstantinidis et al, 2009;Schattenhofer et al, 2009;Quaiser et al, 2010;Swan et al, 2011;Eloe et al, 2011a, b;King et al, 2013). SAR11, or the 'Pelagibacterales,' is a diverse group, spanning at least 18% 16S rRNA gene divergence, and is comprised of subclades with unique spatiotemporal distributions (ecotypes) that follow seasonal patterns (Field et al, 1997;Carlson et al, 2009;Giovannoni and Vergin, 2012;Grote et al, 2012;Vergin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%